One-step synthesis of high surface area N-doped activated carbon for H2S removal from blast furnace gas at low temperature - Houkun Zhu; Bin Meng; Jing Zhao; Siyuan Qu; Heyu Wang; Qianyu Wang; Hao Zhang; Erping Cao; Yuhua Zheng; Yuran Li; Tingyu Zhu; Yanbin Cui (Journal of Environmental Chemical Engineering, 2026)

Preparation and properties of a sodium alginate based gel for dust suppression and moisture regulation - Yanbin Yu; Sai Li; Xiaosong Hou; Bo Zhou; Wenting Cui; Lianxin Fang; Kai Li (Sustainable Chemistry and Pharmacy, 2026)

Full valorization of sugarcane bagasse: Pilot-validated and industrially profitable integrated biorefinery platform - Peng Wu; Xuesong Tan; Quan Zhang; Changlin Miao; Xiaoying Kong; Yanbin Cui; Xueping Song; Chihe Sun; Caifeng Xie; Yongshi Xu; Kai Li; Fubao Sun; et al. (Bioresource Technology, 2026)

Study on seepage characteristics of coal fracture networks based on fractal theory and micro-CT - Wenting Cui; Yanbin Yu; Weimin Cheng; Jie Zang; Zihao Yuan (Bulletin of Engineering Geology and the Environment, 2026)

Hydrological connectivity modulates grassland degradation effects in the yellow river source region - Meng Zhou; Shu Guo; Liyuan Ma; Kening Zhang; Danni Zhou; Qiang Liu; Youqing Yang; Xiuzhu Sun; Yanbin Hao; Xiaoyong Cui; Jianqing Du; Yanfen Wang (Journal of Soils and Sediments, 2026)

Precipitation changes reshape plant-soil microbial biodiversity relationship: differential responses of prokaryotes and fungi in a semi-arid grassland - Meiping Chen; Ruyan Qian; Shaorui Xu; Zhenzhen Zheng; Jianqing Du; Kai Xue; Xiaoyong Cui; Yanfen Wang; Yanbin Hao (CATENA, 2026)

Altered rainfall patterns reshape hillslope water balance and amplify carbon and nitrogen losses in a periglacial grassland - Wencong Lv; Jianqing Du; Liyuan Ma; Fei Wang; Lizhen Cui; Haijun Zhang; Danni Zhou; Qiang Liu; Haishan Niu; Yanbin Hao; Xiaoyong Cui; Yanfen Wang (Journal of Hydrology, 2026)

Pre-oxidating and pre-carbonizing to control the structure of coal tar pitch: The fabrication of N doped hierarchical porous carbon for Zn-ion supercapacitors - Ruiheng Jia; Yiming Liu; Can Xie; Xiao Sun; Zhen Wei; Xiao Li; Yanbin Xu; Yulin Li; Yuming Cui; Shihao Pei (Fuel, 2025)

Efficient removal of H2S from BFG by ZnO and K2CO3 modified activated carbon at room temperature - Liwei Jia; Houkun Zhu; Erping Cao; Chuanfeng Zhao; Yanbin Cui (Journal of Environmental Chemical Engineering, 2025)

Discovery of novel umami peptides and their bitterness masking effects from yellowfin tuna (Thunnus albacares) via peptidomics, multisensory evaluation, and molecular docking approaches - Lai Wei; Cui Shi; Dongcheng Li; Xuan Yuan; Xinyi Yu; Botao Liang; Jiajia Wu; Yiqi Zhang; Zhiyuan Dai; Yanbin Lu; Jing Ye (Food Chemistry, 2025)

Hydrological conditions lead to asynchronised responses of alpine plant communities to temperature changes at the watershed scale - Liyuan Ma; Wencong Lv; Jianqing Du; Qiang Liu; Yanbin Hao; Zhe Pang; Kui Wang; Youqing Yang; Zongsong Wang; Haishan Niu; Xiaoyong Cui; Yanfen Wang (Plant and Soil, 2025)

Negative impacts of rodents on soil microbial diversity and composition modulated by rainfall intensity in a semiarid steppe - Yunqi Xiong; Zhenzhen Zheng; Baofa Yin; Guoliang Li; Xinrong Wan; Ruyan Qian; Linfeng Li; Shuntian Guan; Yuan Liu; Yanfen Wang; Xiaoyong Cui; Jianqing Du; et al. (Applied Soil Ecology, 2025)

A framework for quantifying state transitions in complex ecosystems using energy flow networks - Yanbin Hao; Xin Wang; Tong Zhao; Kai Xue; Jianqing Du; Xiaoyong Cui; Yanfen Wang (Science Bulletin, 2025)

Enhanced HCl resistance of Na-Ce/Al2O3 hydrolysis catalyst to boost blast furnace gas purification - Yuting Lin; Yuran Li; Qiang Cao; Jianshan Wang; Yanbin Cui; Tingyu Zhu (Journal of Cleaner Production, 2025)

Water availability and hydrological connectivity mediate the responses of alpine soil prokaryotes to temperature changes at the watershed scale - Wencong Lv; Liyuan Ma; Jianqing Du; Li Tang; Biao Zhang; Danhong Chen; Qiang Liu; Shutong Zhou; Zhe Pang; Lin Chen; Yanbin Hao; Kai Xue; et al. (Journal of Environmental Management, 2025)

Microbial nitrification inhibitor enhances alpine grassland productivity through narrowing plant niche breadth by utilizing more ammonium - Lizhen Cui; Kai Xue; Junfu Dong; Shun He; Congjia Li; Zhe Pang; Wenjing Liu; Biao Zhang; Shutong Zhou; Kui Wang; Tong Li; Jianqing Du; et al. (Biology and Fertility of Soils, 2025)

Nitrogen addition and rhizosphere effects differentially shape prokaryotic and fungal communities in peanut–maize cropping systems - Yang Chen; Zejin Zhang; Yichao Rui; Carson Pearl; Sheng Lu; Fang Wang; Flemming Ekelund; Yanbin Hao; Xiaoyong Cui (Rhizosphere, 2025)

Nano-flower spherical NiFe LDH adsorbent for efficient removal of H2S in blast furnace gas - Shuwen Peng; Yuran Li; Bin Wang; Yanbin Cui; Jinglei Tian; Hongqiang Liu; Tingyu Zhu (Journal of Hazardous Materials, 2025)

Research on dust suppression technology and structural optimization of cylindrical vortex air curtains based on artificial tornado mechanism - Yanbin Yu; Lianxin Fang; Min Xiang; Wenting Cui; Sai Li; Kezhi Song (Journal of Environmental Chemical Engineering, 2025)

The compounding effect of re-adsorptionon on bioaccessibility of methylmercury in rice-based infant cereals digestion assessment - Xin Wang; Wenbin Cui; Yingjun Wang; Yanbin Li; Bo Meng; Genique Nicolas; Michael Ojeda; Yong Cai (Journal of Environmental Sciences, 2025)

Cross-modal correspondence between visual information and taste: Deciphering the relationship between color and umami using hydrolysates of salmon head as a case study - Cui Shi; Lai Wei; Xuan Yuan; Qianqian Chen; Jing Ye; Jiajia Wu; Zhiyuan Dai; Yanbin Lu (Food Chemistry, 2025)

Selective asymmetric polarization of PAANa “diapers”: Solving the water challenge of prussian blue cathode in organic sodium ion battery - Yuhang Du; Xusheng Wang; Yucheng Zhu; Huanrong Zhang; Mengzhen Wei; Huimin Zhang; Hui Ma; Bao Wang; Yanbin Cui; Junhui Ji; Yonglin He; Kai Song; et al. (Chemical Engineering Journal, 2025)

Towards the Solid-State electrochromic devices: Platform based on transparent and flexible solid polymer electrolyte - Haoming Xu; Imtiaz Haider; Yuhua Zheng; Wenli Li; Serge Zhuiykov; Yanbin Cui (Chemical Engineering Journal, 2025)

Progressive failure characteristics of coal under uniaxial compression: A comprehensive application of micro-ct and digital volume correlation - Yanbin Yu; Chuanwen Ni; Wenting Cui; Weimin Cheng; Yongtao Chen (Bulletin of Engineering Geology and the Environment, 2024)

Warming decouples associations between microbial network complexity and ecosystem multifunctionality in alpine grasslands - Kui Wang; Kai Xue; Wenjing Liu; Biao Zhang; Wenchao Wu; Runchen Zhao; Lizhen Cui; Zongsong Wang; Shutong Zhou; Li Tang; Junfu Dong; Jianqing Du; et al. (Agriculture, Ecosystems & Environment, 2024)

Dynamic Changes and Effects of H2S, IGF-1, and GH in the Traumatic Brain Injury - Zhen Zhang; Xin Wu; Yang Kong; Peng Zou; Yanbin Wang; Hongtao Zhang; Guangqiang Cui; Wei Zhu; Hongguang Chen (Biochemical Genetics, 2024)

Characteristics of bio-tar catalytic cracking by char’s inherent Fe2O3 and K2O for biomass gasification process - Dandan Hu; Duo Sun; Xi Zeng; Fang Wang; Guannan Cui; Yanbin Cui (Fuel, 2024)

Imbibition characteristics and mechanisms of coal using digital image subtraction technique based on Micro-CT - Yanbin Yu; Jinhao Wang; Wenting Cui; Chengwei Gao; Yongtao Chen; Zihao Yuan (Fuel, 2024)

Direct activation and hydrophobic modification of biomass-derived hierarchical porous carbon for toluene adsorption under high humidity - Hao Zhang; Zhixiong Yang; Erping Cao; Yuhua Zheng; Qiang Ren; Yanbin Cui (Chemical Engineering Journal, 2024)

Evolution rules of coal mesopore structure under the action of hydraulic coupling - Yanbin Yu; Ruoyu Mu; Weimin Cheng; Wenting Cui; Yongtao Chen (Bulletin of Engineering Geology and the Environment, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Decoding wettability in coal-water-CO2 system for enhanced sequestration security - Chao Cui; Yanbin Yao; Dameng Liu; Xiaoxiao Sun (Gas Science and Engineering, 2024)

Extreme drought alters methane uptake but not methane sink in semi-arid steppes of Inner Mongolia - Fuqi Wen; Joel A. Biederman; Yanbin Hao; Ruyan Qian; Zhenzhen Zheng; Xiaoyong Cui; Tong Zhao; Kai Xue; Yanfen Wang (Science of The Total Environment, 2024)

Microstructure evolution law and dissolution time effect of bituminous coal under acetic acid acidification: Based on Micro-CT image analysis - Yanbin Yu; Hao Xing; Weimin Cheng; Wenting Cui; Yongtao Chen (Fuel, 2024)

Methane uptake responses to extreme droughts regulated by seasonal timing and plant composition - Zhenzhen Zheng; Fuqi Wen; Joel A. Biederman; Muyesaier Tudi; Mengbo Lv; Shaorui Xu; Xiaoyong Cui; Yanfen Wang; Yanbin Hao; Linfeng Li (CATENA, 2024)

Transgenerational effects of extracts containing Microcystin-LR exposure on reproductive toxicity and offspring growth inhibition in a model organism zebrafish - Qing Yang; Lanlan Huang; Ning Yang; Hongyang Cui; Yanbin Zhao; Zipeng Li; Yindong Tong (Aquatic Toxicology, 2024)

Differences in background environment and fertilization method mediate plant response to nitrogen fertilization in alpine grasslands on the Qinghai-Tibetan Plateau - Shun He; Jianqing Du; Yanfen Wang; Lizhen Cui; Wenjing Liu; Yifan Xiao; Qinwei Ran; Linfeng Li; Zuopei Zhang; Li Tang; Ronghai Hu; Yanbin Hao; et al. (Science of The Total Environment, 2024)

Fracture and porosity evolution of coal under uniaxial compression: An in-situ X-ray tomography study - Yanbin Yu; Zhaoxu Qiu; Weimin Cheng; Qi Yang; Wenting Cui; Kang Rong; Yunfei Li (Geomechanics for Energy and the Environment, 2023)

Effects of extra-extreme precipitation variability on multi-year cumulative nitrous oxide emission in a semiarid grassland - Linfeng Li; Yanbin Hao; Weijin Wang; Joel A. Biederman; Zhenzhen Zheng; Yanfen Wang; Muyesaier Tudi; Ruyan Qian; Biao Zhang; Rongxiao Che; Xiaoning Song; Xiaoyong Cui; et al. (Agricultural and Forest Meteorology, 2023)

Unraveling the consequences of nitrogen addition on soil phosphorus fractions in alpine grasslands: insights from field experiments and global analysis - Wenchao Wu; Lili Jiang; Tong Li; Touhami Driss; Zhihong Xu; Yanbin Hao; Xiaoyong Cui (Journal of Soils and Sediments, 2023)

Extracellular enzyme activities response to nitrogen addition in the rhizosphere and bulk soil: A global meta-analysis - Yang Chen; Anquan Xia; Zejin Zhang; Fang Wang; Jianhui Chen; Yanbin Hao; Xiaoyong Cui (Agriculture, Ecosystems & Environment, 2023)

Navigating the landscape of global sustainable livelihood research: past insights and future trajectory - Tong Li; Ranjay K. Singh; Lizhen Cui; Zhihong Xu; Hongdou Liu; Francesco Fava; Shalander Kumar; Xiufang Song; Li Tang; Yanfen Wang; Yanbin Hao; Xiaoyong Cui (Environmental Science and Pollution Research, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

Effects of different laying periods on airborne bacterial diversity and antibiotic resistance genes in layer hen houses - Huan Cui; Cheng Zhang; Kui Zhao; Juxiang Liu; Jie Pu; Yunyi Kong; Shishan Dong; Ligong Chen; Yanbin Zhao; Yanyan Chen; Zhaoliang Chen; Lei Zhang; et al. (International Journal of Hygiene and Environmental Health, 2023)

Water-based green and sustainable extraction protocols for value-added compounds from natural resources - Yating Jin; Di Hu; Qianqian Chen; Cui Shi; Jing Ye; Zhiyuan Dai; Yanbin Lu (Current Opinion in Green and Sustainable Chemistry, 2023)

Dissolved rare earth elements in the Northwest Pacific: Sources, water mass tracing, and cross‐shelf fluxes - Axiang Cao; Jing Zhang; Honghai Zhang; Zhaohui Chen; Guanghao Cui; Zhensong Liu; Yanbin Li; Qian Liu (Frontiers in Marine Science, 2023)
In the Northwest Pacific, a key area for understanding the sources and transport of materials in the ocean, knowledge of the sources, transport, and biogeochemical cycling of trace elements is limited. Trace elements such as the rare earth elements (REEs) can trace the sources and transport of water masses. Here we present dissolved REE concentrations along a longitudinal transect (150 o E) from 13°N to 40°N in the Northwest Pacific (≤2000 m). We divided the transect into two subregions: a mixed water region (MWR; 37~40 °N, where the Oyashio and Kuroshio currents mix) and a subtropical region (13~34 °N). In the MWR, REEs were strongly positively correlated with apparent oxygen utilization in subsurface water (depth > the chlorophyll maximum layer, potential density <26.6 kg/m 3 ), with about a 4-fold higher slope (0.15±0.06) than in the subtropical region in subsurface and intermediate waters (0.04±0.003, potential density <27.5 kg/m 3 ). This suggests that REEs are released by organic matter remineralization at a higher efficiency in the MWR vs. in the subtropical region, which can be explained by different water masses and plankton community structures. In addition, we observed a lithogenic input signal of REEs from the Aleutian Islands based on the high La/Yb ratio (>0.35). This ratio was controlled by lateral transport and showed a good agreement with salinity, indicating that it is a useful tracer of low salinity water originating from the subarctic region. Furthermore, we estimated the cross-shelf fluxes of Nd in the Northwest Pacific. The estimated Nd fluxes from the Sea of Okhotsk, the Sea of Japan, the East China Sea, and the South China Sea into the Northwest Pacific were 29~32 t/y, 159~302 t/y, 142~616 t/y, and -298~34 t/y, respectively. This study highlights the importance of considering the cross-shelf REE fluxes in the Northwest Pacific when constructing the oceanic REE budgets.

Grasslands Maintain Stability in Productivity Through Compensatory Effects and Dominant Species Stability Under Extreme Precipitation Patterns - Wenlan Gao; Linfeng Li; Seth M. Munson; Xiaoyong Cui; Yanfen Wang; Yanbin Hao (Ecosystems, 2022)

Characteristics and trends of grassland degradation research - Tong Li; Lizhen Cui; Michele Scotton; Junfu Dong; Zhihong Xu; Rongxiao Che; Li Tang; Shuohao Cai; Wenchao Wu; Davide Andreatta; Yanfen Wang; Xiufang Song; et al. (Journal of Soils and Sediments, 2022)

Isolation and phylogenetic analysis of strains of feline calicivirus in Beijing, China - Zhaoyang Wang; Ting Xin; Jin Wei; Yajun Jiang; Xueting Liu; Wenjing Song; Xiaoyu Guo; Weifeng Yuan; Yanbin Cui; Hongfei Zhu; Hong Jia (Archives of Virology, 2021)

miR-9-5p facilitates hepatocellular carcinoma cell proliferation, migration and invasion by targeting ESR1 - Libing Wang; Mingxin Cui; Daming Cheng; Fengzhi Qu; Jingkun Yu; Yanbin Wei; Ling Cheng; Xiaotang Wu; Xiaogang Liu (Molecular and Cellular Biochemistry, 2021)

A novel compound wind speed forecasting model based on the back propagation neural network optimized by bat algorithm - Yanbin Cui; Chenchen Huang; Yanping Cui (Environmental Science and Pollution Research, 2020)

Terrestrial N 2 O emissions and related functional genes under climate change: A global meta‐analysis - Linfeng Li; Zhenzhen Zheng; Weijin Wang; Joel A. Biederman; Xingliang Xu; Qinwei Ran; Ruyan Qian; Cong Xu; Biao Zhang; Fang Wang; Shutong Zhou; Lizhen Cui; et al. (Global Change Biology, 2020)
Nitrous oxide (N 2 O) emissions from soil contribute to global warming and are in turn substantially affected by climate change. However, climate change impacts on N 2 O production across terrestrial ecosystems remain poorly understood. Here, we synthesized 46 published studies of N 2 O fluxes and relevant soil functional genes (SFGs, that is, archaeal amoA , bacterial amoA , nosZ , narG , nirK and nirS ) to assess their responses to increased temperature, increased or decreased precipitation amounts, and prolonged drought (no change in total precipitation but increase in precipitation intervals) in terrestrial ecosystem (i.e. grasslands, forests, shrublands, tundra and croplands). Across the data set, temperature increased N 2 O emissions by 33%. However, the effects were highly variable across biomes, with strongest temperature responses in shrublands, variable responses in forests and negative responses in tundra. The warming methods employed also influenced the effects of temperature on N 2 O emissions (most effectively induced by open‐top chambers). Whole‐day or whole‐year warming treatment significantly enhanced N 2 O emissions, but daytime, nighttime or short‐season warming did not have significant effects. Regardless of biome, treatment method and season, increased precipitation promoted N 2 O emission by an average of 55%, while decreased precipitation suppressed N 2 O emission by 31%, predominantly driven by changes in soil moisture. The effect size of precipitation changes on nirS and nosZ showed a U‐shape relationship with soil moisture; further insight into biotic mechanisms underlying N 2 O emission response to climate change remain limited by data availability, underlying a need for studies that report SFG. Our findings indicate that climate change substantially affects N 2 O emission and highlights the urgent need to incorporate this strong feedback into most climate models for convincing projection of future climate change.

Extreme-duration drought impacts on soil CO2 efflux are regulated by plant species composition - Chaoting Zhou; Joel A. Biederman; Hui Zhang; Linfeng Li; Xiaoyong Cui; Yakov Kuzyakov; Yanbin Hao; Yanfen Wang (Plant and Soil, 2019)

Using landscape indicators and Analytic Hierarchy Process (AHP) to determine the optimum spatial scale of urban land use patterns in Wuhan, China - Qiuping Huang; Jiejun Huang; Yunjun Zhan; Wei Cui; Yanbin Yuan (Earth Science Informatics, 2018)

A fractal and entropy-based model for selecting the optimum spatial scale of soil erosion - Lemeng Ren; Jiejun Huang; Qiuping Huang; Guangdi Lei; Wei Cui; Yanbin Yuan; Youjia Liang (Arabian Journal of Geosciences, 2018)

Using the DNDC model to simulate the potential of carbon budget in the meadow and desert steppes in Inner Mongolia, China - Xuan Wu; Xiaoming Kang; Wenjun Liu; Xiaoyong Cui; Yanbin Hao; Yanfen Wang (Journal of Soils and Sediments, 2018)

Precipitation drives the biogeographic distribution of soil fungal community in Inner Mongolian temperate grasslands - Di Wang; Yichao Rui; Kai Ding; Xiaoyong Cui; Yanbin Hao; Li Tang; Zhe Pang; Biao Zhang; Shutong Zhou; Kui Wang; Yanfen Wang (Journal of Soils and Sediments, 2018)

Modeling Carbon Fluxes Using Multi-Temporal MODIS Imagery and CO2 Eddy Flux Tower Data in Zoige Alpine Wetland, South-West China - Xiaoming Kang; Yanfen Wang; Huai Chen; Jianqing Tian; Xiaoyong Cui; Yichao Rui; Lei Zhong; Paul Kardol; Yanbin Hao; Xiangming Xiao (Wetlands, 2014)

Responses of soil respiration and its components to drought stress - Yanfen Wang; Yanbin Hao; Xiao Yong Cui; Haitao Zhao; Chengyuan Xu; Xiaoqi Zhou; Zhihong Xu (Journal of Soils and Sediments, 2014)

Effects of grazing on CO2 balance in a semiarid steppe: field observations and modeling - Xiaoming Kang; Yanbin Hao; Xiaoyong Cui; Huai Chen; Changsheng Li; Yichao Rui; Jianqing Tian; Paul Kardol; Lei Zhong; Jinzhi Wang; Yanfen Wang (Journal of Soils and Sediments, 2013)

Effects of warming and increased precipitation on soil carbon mineralization in an Inner Mongolian grassland after 6 years of treatments - Xiaoqi Zhou; Chengrong Chen; Yanfen Wang; Zhihong Xu; Zhengyi Hu; Xiaoyong Cui; Yanbin Hao (Biology and Fertility of Soils, 2012)

Modeling impacts of climate change on carbon dynamics in a steppe ecosystem in Inner Mongolia, China - Xiaoming Kang; Yanbin Hao; Changsheng Li; Xiaoyong Cui; Jinzhi Wang; Yichao Rui; Haishan Niu; Yanfen Wang (Journal of Soils and Sediments, 2011)

The response of ecosystem CO2 exchange to small precipitation pulses over a temperate steppe - Yanbin Hao; Yanfen Wang; Xurong Mei; Xiaoyong Cui (Plant Ecology, 2010)